Climate Change and the Occurrence of Harmful Microorganisms in Florida’s Ocean and Coastal Waters - Karl Havens (EDIS)
Climate change is expected to result in increased temperatures of nearshore ocean water, and this could lead to increased growth of harmful microorganisms. These include algae that form noxious or toxic blooms, including red tides, and bacteria and other pathogens. This situation could have negative consequences in regard to human health and also Florida’s ocean-related economy. This 6-page fact sheet discusses projected ocean temperatures, how harmful microorganisms living in the ocean might respond, and how this might affect people, and identifies actions that could be taken to reduce these impacts. Written by Karl Havens, and published by Florida Sea Grant, June 2015.